A concentrated solar still for community scale desalination. - Bahrami, Mohammadali (Parsa) (Cranfield University, 2018)
Water and energy are two main basic elements that human lives are dependent on to improve our life standards. Unreliability and a lack of safe drinking water source constitute a major difficulty in developing countries. Among many water purification technologies, solar desalination/distillation has become one of the best solutions as the most attractive and sustainable method to supply drinkable water in remote areas at reasonable cost for future generations. Seawater desalination technologies needed substantial amount of energy in order to convert brackish water into drinkable water. Thus, an extensive research on many desalination technologies has taken place in the last few decades, and solar desalination technology has become one of the most favourable sustainable methods to provide fresh water of sufficiently high quality for human communities. However, this method is not commercialized yet due to its low productivity, but improving this t has become a great source of interest for many researchers. A solar still consumes direct solar energy to produce distilled water through evaporation and condensation process of brackish water. Much research has been conducted in order to increase the productivity, but the outcomes mostly require complex components and a notable increase in cost. Consequently, developing a productive, compact, easy to operate and reasonable cost solar distillation unit was the main challenge in this body of work. A comprehensive literature review is presented in order to illustrate different modifications and their properties on the productivity of solar stills. Even though there are considerations, which cannot be controlled by human intervention (such as meteorological parameters), design and operational factors could make a direct influence on the productivity of the solar still. A novel transportable single basin, double slope shape solar still, enhanced with an internal ventilation fan connected to a copper material heat exchanger, was designed and built without forsaking its basic remit order to increase both evaporation and condensation process. The unit was also designed to use two linear focused Fresnel lenses as a solar radiation concentrator to direct radiation onto the top of solar still basin area. A detailed comparison of theoretical and laboratory experimental results were obtained for the present solar still to find the influence of different modification factors to the present solar still productivity. The temperatures of different parts of the solar still unit such as basin water, top cover glasses, heat exchanger condenser etc. were measured to evaluate different modifications including different fan airflow ratios, with and without a fan shroud, and lava stone effects to the distillate water output. The results presented an increase in productivity of 25.73% in comparison with a conventional solar still, by using a ventilation exhaust fan at its maximum airflow. Also an increase of 16.3% was also achieved by using lava stone as a heat storage material in the basin area.
Keywords: Solar distillation; productivity enhancement; ventilation fan; heat storing material; heat transfer; design and operational parameters